2012
DOI: 10.1186/1742-2094-9-192
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-I is an APOE genotype-dependent suppressor of glial activation

Abstract: BackgroundInheritance of the human ϵ4 allele of the apolipoprotein (apo) E gene (APOE) significantly increases the risk of developing Alzheimer’s disease (AD), in addition to adversely influencing clinical outcomes of other neurologic diseases. While apoE isoforms differentially interact with amyloid β (Aβ), a pleiotropic neurotoxin key to AD etiology, more recent work has focused on immune regulation in AD pathogenesis and on the mechanisms of innate immunomodulatory effects associated with inheritance of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…The statistically significant decrease in the expression of the APOC1 gene in severe PE, which was revealed in the present study, is probably due to the development of oxidative stress in the blood vessels of the placenta or the recently discovered immunosuppressive properties of the C1 apolipoprotein encoded by this gene [52]. It was previously shown that the serum of PE patients has a high level of triglyceride-rich lipoproteins, which can promote endothelial dysfunction [53, 54].…”
Section: Discussionsupporting
confidence: 63%
“…The statistically significant decrease in the expression of the APOC1 gene in severe PE, which was revealed in the present study, is probably due to the development of oxidative stress in the blood vessels of the placenta or the recently discovered immunosuppressive properties of the C1 apolipoprotein encoded by this gene [52]. It was previously shown that the serum of PE patients has a high level of triglyceride-rich lipoproteins, which can promote endothelial dysfunction [53, 54].…”
Section: Discussionsupporting
confidence: 63%
“…The most significant change due to aging is observed in gene expression levels of APOD [85]; CSF and hippocampal apoD levels are elevated in Alzheimer's disease [86] and correlated with disease severity [87]. ApoC-I colocalizes with amyloid-b plaques in human Alzheimer's disease brain [88], has been suggested to influence neuroinflammation in Alzheimer's disease [89], and may contribute to genetic susceptibility possibly via linkage disequilibrium with APOE e4 [89][90][91]. In Alzheimer's disease mice, Apoa4 deficiency increases amyloid-b load, enhances neuronal loss, accelerates cognitive dysfunction, and increases mortality [92].…”
Section: Key Pointsmentioning
confidence: 98%
“…ApoC1 is coded on chromosome 19q13.32, it is involved in lipoprotein metabolism and because of alternative splicing many transcript variants exist. The gene is activated when monocytes differentiate into macrophages and ApoC1 expression has been shown in cerebral tissue [9].…”
Section: Resultsmentioning
confidence: 99%